Improving Student Learning Outcomes in Thematic Learning Using the Problem-Solving Model - Pramesti, Tessa; Yulimarta, Esa; Martaliza, Yelly (Strata Social and Humanities Studies, 2024)
Class IV students at SD Negeri 14/III Punai Merindu face thematic learning difficulties in Indonesian and natural science subjects. These difficulties arise because, first, the teacher's lack of creativity in designing learning models. Second, teachers are not optimal in using learning models, methods and media that are appropriate to the learning material. Researchers intend to overcome students' learning difficulties in thematic learning in Indonesian and natural science subjects by using the Problem-Solving model. This type of research is PTK. The subjects of this research were fourth grade students at SD Negeri 14/III Punai Merindu, West Lake Kerinci District, Kerinci Regency in semester 1 of the 2023/2024 academic year. This research was conducted in 2 cycles. Each cycle held 2 meetings. At the end of each meeting, a written test was carried out in the form of essays and short essays to see improvements in student learning outcomes. Researchers succeeded in improving the thematic learning outcomes of class IV students in Indonesian language subjects in cycle I (27%) and cycle II (82%). Completeness in science subjects cycle I (36%) and cycle II (91%). The average value of observations of teacher activities in cycle I was (74%) and cycle II (93%). The results of observations of student activities in cycle I were average (62%) and cycle II (89%). So, it can be concluded that the Problem-Solving learning model is successful in improving student thematic learning outcomes.